Prevention of Exposure Keratopathy in Critically Ill Patients: A Single-Center, Randomized, Pilot Trial Comparing Ocular Lubrication With Bandage Contact Lenses and Punctal Plugs. Issue 11 (November 2017) - Bendavid, Itai; Avisar, Inbal; Serov Volach, Irena; Sternfeld, Amir; Dan Brazis, Idit; Umar, Lewaa; Yassur, Yiftach; Singer, Pierre; Cohen, Jonathan David
Abstract : Objectives: To compare the effectiveness of bandage contact lenses and punctal plugs with ocular lubricants in preventing corneal damage in mechanically ventilated and sedated critically ill patients. Design: Single-center, prospective, randomized, pilot study. Setting: Sixteen-bed, general ICU at a tertiary academic medical center. Patients: Adults admitted to the ICU and anticipated to require mechanical ventilation and continuous sedation for greater than or equal to 4 days. Interventions: Patients were randomized to receive eye care with ocular lubricants ( n = 38), bandage contact lenses ( n = 33), or punctal plugs ( n = 33). The bandage contact lenses were changed every 4 days, whereas the punctal plugs remained in situ for the entire study. Measurements and Main Results: The primary endpoint was the presence or absence of corneal damage as assessed by the grade of keratopathy. Patients were examined by an ophthalmologist blinded to the study group every 4 days and at the time of withdrawal from the study, due to cessation of sedation, discharge from the ICU, or death. The mean duration of the study was 8.6 ± 6.2 days. The grade of keratopathy in the ocular lubricant group increased significantly in both eyes ( p = 0.01 for both eyes) while no worsening was noted in either the lens or punctal plugs groups. In a post hoc analysis of patients with an initially abnormal ophthalmic examination, significant healing of keratopathy was noted in the lens group ( p = 0.02 and 0.018 for left and right eyes, respectively) and in the right eye of the plugs group ( p = 0.005); no improvement was noted in the ocular lubricant group. Conclusions: Compared with ocular lubrication, bandage contact lenses and punctal plugs were more effective in limiting keratopathy, and their use, particularly of bandage contact lenses, was associated with significant healing of existing lesions. Abstract : Supplemental Digital Content is available in the text.